The effect of supplementation with three lactic acid bacteria from bovine origin on growth performance and health status of young calves - Frizzo, Laureano Sebastian (2008)
Good health in animals that are to be part of human diet during the production chain is key from both production and public health points of view. The use of indigenous microorganisms with probiotic capacity is an alternative for treating and preventing several bovine diseases. This study presents an assessment of the effect of a lactic acid bacteria inoculum from bovine origin integrated by Lactobacillus casei DSPV 318T, Lactobacillus salivarius DSPV 315T and Pediococcus acidilactici DSPV 006T on growth performance and health status of young calves. The 3-microorganism inoculum suspended in a solution of NaCl 0,15M was administered to an experimental group of calves at a daily dose of 109 UFC KgG1 for 35 days. A control group was administered NaCl solution as placebo. The inoculum showed no significant effects, either positive or negative, on the animals´ performance that could have been measured in the conditions in which the study was developed. Perhaps, the lack of evident beneficial effects may have been due to the excellent health status of the animals, the appropriate environmental conditions of the test and the absence of stressing situations during breeding. All evidence shows that the advantages of using probiotics as regards growth performance, health improvement and calf survival could be more easily detected in farms presenting high morbidity and mortality rates mainly produced by diarrhoea syndrome.